Ориньяк Большого Северного Причерноморья: обзор общих и особенных индустриально-хронологических характеристик - Демиденко, Ю.Э. (Археологический альманах, 2009)
The article deals with materials of 6 sites with Aurignacian complexes in the Great North Black sea region, the southern continuous belt of Eastern Europe during Last Interpleniglacial. According to the artefact data, it is possible to recognize both Aurignacian 0 / Archaic Aurignacian and Evolved Aurignacian complexes in this region. The Aurignacian 0 / Archaic Aurignacian industry is represented by assemblages from Siuren I rock-shelter (Crimea), the 1920s excavations lower layer / the 1990s excavations Units H and G, Chulek I site (Lower Don area), Kamennomostskaya cave, lower layer and Shyrokiy Mys site (North-Western Caucasus). While the Siuren I and Chulek I Aurignacian 0 / Archaic Aurignacian assemblages are the direct analogies in the respective Western and Central European Aurignacian assemblages, the Kamennomostskaya cave and Shyrokiy Mys materials do point out some certain typological parallels with Levantine Early Aurignacian. The Evolved Aurignacian industry is known through materials from Siuren I rock-shelter (Crimea), the 1920s excavations middle layer / the 1990s excavations Unit F, Gubskiy rockshelter I, lower Upper Palaeolithic layer and Monasheskaya cave, some Upper Palaeolithic flints redeposited with Middle Paleolithic cultural bearing sediments (North-Western Caucasus). And again, the artefact studies put the Siuren I materials into the context of European Evolved Aurignacian, whereas the Gubskiy I finds may have industrial connections with Levantine Aurignacian.